2014
DOI: 10.1017/s1751731114000603
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of artificially reared Romane lambs

Abstract: A consequence of increasing litter size in sheep is that a portion of the lambs have to be reared artificially. Detailed information about the pattern of milk consumption of artificially reared lambs would help improve their management. The purpose of this study is to describe the individual and group feeding behaviour of 94 Romane artificially reared lambs from 5 to 28 days of age using an electronic automatic lamb feeder. Animals were located in four pens of 8 to 15 lambs of similar age with one teat per pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…For example, de Passillé et al (2016) reported a large range in milk intakes during the first 2 to 4 days of age in Holstein dairy calves, ranging from 2.4 l to 12 l/day (7 to 30% of BW), resulting in differences in BW gains (ranging from 0.07 to 1.2 kg/day in the first month of age). Similar variability in milk feeding patterns were reported for artificially-reared lambs, ranging from 0.3 to 2.9 l/day milk consumption (David et al, 2014).…”
Section: Development Of Feeding Behavioursupporting
confidence: 75%
“…For example, de Passillé et al (2016) reported a large range in milk intakes during the first 2 to 4 days of age in Holstein dairy calves, ranging from 2.4 l to 12 l/day (7 to 30% of BW), resulting in differences in BW gains (ranging from 0.07 to 1.2 kg/day in the first month of age). Similar variability in milk feeding patterns were reported for artificially-reared lambs, ranging from 0.3 to 2.9 l/day milk consumption (David et al, 2014).…”
Section: Development Of Feeding Behavioursupporting
confidence: 75%
“…The intersection between the two Gaussian distributions (the “within‐meal BVT distribution” and the “between‐meal BVT distribution”) defining the cut‐off point (or meal criterion) was 44 min 57 s. All visits separated by a time interval of <45 min were therefore grouped together as a single meal, while visits separated by time intervals of more than 45 min were recorded as separate meals. With a mixture of two Gaussian distributions, David, Bouvier, Ricard, Ruesche, and Weisbecker () obtained a meal criterion of 49 min with artificially reared young Romane lambs, whereas Tolkamp and Kyriazakis () estimated a cut‐off of approximately 30 min for lactating dairy cows. Yeates, Tolkamp, Allcroft, and Kyriazakis () pointed out that the meal criteria depended on the number of Gaussian distributions fitted and the types of distribution (Normal vs. Weibull) and could thus vary between 22 and 29 min in dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
“…In case of artificial rearing conditions, calves are mostly fed via bucket and sometimes by artificial teat to exhibit natural sucking behavior [ 2 ]. The artificial rearing of animals represents a combination of emotional (separation from the dam) and nutritional (transition from maternal milk to a commercial milk substitute) stressors in different species [ 3 , 4 ]. It has been suggested that rearing in contact with the mother during the first 12 weeks, even if very limited, may have a positive effect on behavior of heifer when introduced into the dairy herd, as various non-nutritive abnormal oral activities, including self-grooming and tongue playing and cross-sucking have been found to occur in calves fed with a bucket or reared in individual pen [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%